2011
DOI: 10.1007/s10059-011-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

Inonotus obliquus Protects against Oxidative Stress-Induced Apoptosis and Premature Senescence

Abstract: In this study, we investigated the cytoprotective effects of Inonotus obliquus against oxidative stress-induced apoptosis and premature senescence. Pretreatment with I. obliquus scavenged intracellular ROS and prevented lipid peroxidation in hydrogen peroxide-treated human fibroblasts. As a result, I. obliquus exerted protective effects against hydrogen peroxide-induced apoptosis and premature senescence in human fibroblasts. In addition, I. obliquus suppressed UV-induced morphologic skin changes, such as skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Yun et al () reported that I. obliquus extracts ameliorated oxidative stress, inhibited lipid peroxidation, and repressed premature senescence in human fibroblasts by suppressing the activities of MMP‐1 and MMP‐9 and enhancing the production of collagen in in vivo hairless mice. The freeze dried extracts of I. obliquus scavenged DPPH free radicals in a dose‐dependent manner and exhibited a higher superoxide radical scavenging activity when compared with L‐ascorbic acid (Cui et al, ).…”
Section: Influence Of I Obliquus Extract On the Immune Systemmentioning
confidence: 99%
“…Yun et al () reported that I. obliquus extracts ameliorated oxidative stress, inhibited lipid peroxidation, and repressed premature senescence in human fibroblasts by suppressing the activities of MMP‐1 and MMP‐9 and enhancing the production of collagen in in vivo hairless mice. The freeze dried extracts of I. obliquus scavenged DPPH free radicals in a dose‐dependent manner and exhibited a higher superoxide radical scavenging activity when compared with L‐ascorbic acid (Cui et al, ).…”
Section: Influence Of I Obliquus Extract On the Immune Systemmentioning
confidence: 99%
“…Numerous studies have tested the effects of solar radiation and oxidative stress on the skin [ 29 , 83 , 84 , 85 ], and oxidative stress has been linked to age-related loss of skin elasticity [ 86 , 87 , 88 ], defective cellular signaling [ 68 ] and photoaging [ 89 , 90 ]. Because it triggers cellular damage pathways, oxidative stress activates cellular senescence which is thought to directly lead to photoaging [ 91 , 92 , 93 , 94 ]. Cellular senescence is associated with a reduced capacity to divide and proliferate, sometimes in conjunction with shortening of telomeres [ 95 , 96 , 97 , 98 ].…”
Section: Oxidative Stress and Agingmentioning
confidence: 99%
“…For instance, water and ethanolic extracts of chaga protected H 2 O 2 -treated human lymphocyte from DNA damage (Najafzadeh et al, 2007;Park et al, 2005a;Park et al, 2004). Besides, water extracts of chaga also prevented H 2 O 2 -induced apoptosis and premature senescence in human fibroblasts, it functioned through scavenging intracellular ROS (reactive oxygen species), preventing lipid peroxidation, and increasing collagen synthesis through inhibition of MMP-1 and MMP-9 activities (Yun et al, 2011). Recently, Szychowski et al (2018) found that chaga extract enhanced the antioxidative stress ability of normal cells but induced oxidative stress to cancer cells.…”
Section: Antioxidant Effectsmentioning
confidence: 99%